Clinical Performance of Hydrogel-based Dressing in Facial Burn Wounds: A Retrospective Observational Study. (February 2021) - Ou, Kuang-Ling; Tzeng, Yuan-sheng; Chiao, Hao-Yu; Chiu, Han-ting; Chen, Chun-Yu; Chu, Tzi-Shiang; Huang, Dun-Wei; Hsu, Kuo-Feng; Chang, Chun-Kai; Wang, Chih-Hsin; Dai, Niann-Tzyy; Wu, Chien-Ju
Abstract : Abstract: Preserving both esthetic and functional outcome remains challenging in facial burn injuries. The major issue is the initial treatment of injury. In this study, we focused on patients with partial-thickness facial burns admitted to the burn unit of Tri-Service General Hospital, Taipei, from November 2016 to November 2018. In 21 included patients, customized mask-style, transparent hydrogel-based dressing was applied to the burns. The mean age of included patients was 37.4 years. The mean area of burn injury was 11.9% of total body surface area, and the mean area of second-degree facial burns was 162.3 cm 2 . Full reepithelialization took, on average, 10.86 days. Scarring was acceptable in terms of texture and color, and no hypertrophic or keloidal scarring was noted. The mean Vancouver Scar Scale score was 2.07. Use of the hydrogel-based dressing masks seems to be a promising means of reducing pain, providing uninterrupted wound healing, facilitating observation, and positively affecting scarring in patients with second-degree facial burns.